Energy Absorption Study of Aluminium Profiles with Variety of Filling Configurations - BOGUSZ, Paweł; STANKIEWICZ, Michał; SŁAWIŃSKI, Grzegorz (Engineering Transactions, 2017)
The subject of this paper is research of thin-walled aluminium profiles filled with different materials and subjected to dynamic load. The aim of this study was to determine the crashworthiness capabilities of the tested elements. Such structures can be used as elements minimalising the effects of blast wave load on military vehicles and occupants carried thereon. The blast wave generated during the explosion of explosives, especially improvised explosive devices(IED), under or near a combat vehicle poses a deadly threat to the crew and passengers inside the vehicle. The idea of installing crashworthy structures in a vehicle seat to protect the crew and passengers is not new. It was found useful in aviation, automotive or railway industry. In this paper, circular aluminium profiles of an external diameter of 50 mm and thickness of 2 mm were investigated. They were filled with three kinds of materials: cork, foamed aluminium of low density and foamed aluminium of high density. The dynamic tests were performed on a spring hammer apparatus. The energy absorbing structures and materials used to fill the aluminium profiles were examined separately in static compression tests. The characteristics of force-displacement response of the investigated structures were determined, compared and analysed. The energy absorbing characteristic parameters were obtained and discussed to determine the best option.